Sosialisasi Strategi Meningkatkan Literasi Minat Baca melalui Pojok Baca di Desa Gunung Menyan, Kecamatan Pamijahan, Kabupaten Bogor - Musyaropah, Wardatul; Suryani, Ermi; Amalia, Nurul; Sundari, Deva Sri; Mukri, Rusdiono (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2025)
This community service is carried out to grow and develop reading literacy in the general public. With the procurement of a library and the development carried out, it fosters interest in reading in the Mt. Menyan, District. Pamijahan. This service is carried out first by using a descriptive qualitative approach. This service is an attempt to link the research process into the process of social change. The low interest in reading in the community was resolved with a solution for the procurement of a Mini Village Library called the